2010
DOI: 10.1158/1078-0432.ccr-09-2658
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Localization of Signal Transducer and Activator of Transcription 3 in Head and Neck Squamous Cell Carcinoma Is Associated with a Better Prognosis

Abstract: Purpose: A high frequency of head and neck squamous cell cancers (HNSCC) contain constitutively activated signal transducer and activator of transcription 3 (STAT3). To further elucidate the prognostic role of STAT3 in HNSCC, the expression pattern of STAT3 was correlated with outcome in two independent data sets.Experimental Design: STAT3 protein expression analysis was done on a test cohort of 102 patients with HNSCC recruited between 1992 and 2005. Automated quantitative analysis was used to assess STAT3 pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 30 publications
2
51
0
1
Order By: Relevance
“…6E). Importantly, our findings may explain the accumulating controversies regarding the tumor suppressor function of STAT3 in various cancer types (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). For instance, there are many publications in which the immune-detection of pSTAT3 Y705 or nuclear STAT3 was found to significantly correlate with a better outcome (9)(10)(11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…6E). Importantly, our findings may explain the accumulating controversies regarding the tumor suppressor function of STAT3 in various cancer types (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). For instance, there are many publications in which the immune-detection of pSTAT3 Y705 or nuclear STAT3 was found to significantly correlate with a better outcome (9)(10)(11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 61%
“…The oncogenic potential of STAT3 has been well documented; specifically, the constitutively activated STAT3 mutant (commonly labeled STAT3C) can effectively induce malignant transformation (4), and many human cancers harbor constitutively active STAT3 (1)(2)(3). Nevertheless, accumulating evidence from both experimental and clinical studies has suggested that STAT3 may also carry a tumor suppressor role in specific contexts (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). For instance, in a mouse model of intestine adenoma, tissue-specific STAT3 gene knockout was found to enhance tumor invasion and promote tumor progression (5,6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, after being identified as an oncogene in some cancer types, 31,33 recent work has highlighted its role as tumor suppressor in glioma, hepatoma, breast, intestinal, head and neck and thyroid cancer. 11,30,[34][35][36][37][38] Interestingly, Couth et al 11 found that an autocrine IL6/gp130/JAK loop is responsible for keeping high levels of phospho-STAT3 phosphorylation in thyroid carcinoma cell lines, which in turn suppress tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…TMAs were deparaffinized and stained as previously described (14). In brief, slides were deparaffinized in 2 changes of xylene and rehydrated through changes of ethanol with decreasing concentrations.…”
Section: Quantitative Ihcmentioning
confidence: 99%